A longitudinal case study on the use of the abstract noun in English compositions among students of Sekolah Menengah Imtiaz Kuala Terengganu, Terengganu / Norliana Mohd Noor - Mohd Noor, Norliana (2015)
This longitudinal case study investigated the use of abstract nouns in English compositions written over four years by young learners of English. A total of 80 compositions were collected from four secondary school students of IMTIYAZ in Kuala Terengganu, Terengganu. Per year, each respondent contributed five compositions written for their English subject from Form One till Form Four. A mixture of quantitative and qualitative approaches was used to analyze the data. The findings showed that all four respondents had a major increase in the number of occurrences of the abstract noun between Form 1 to Form 2 but the occurrences stabilized in later years. All the respondents were able to use the abstract noun fairly well in their English compositions. Where the errors were concerned, the respondents displayed inflectional type of error more frequently than derivational type of error with these abstract nouns over the years. This study has shed light to the students’ improvement in English grammar. This will be very useful to teachers in secondary schools in Malaysia to examine their students’ writing performance. This study will contribute lot to those who write textbooks and syllabus especiafiy on inflections and derivations.